OPTIMASI PENCAHAYAAN ALAMI PADA STUDIO ARSITEKTUR DI UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Masruchin, Febby Rahmatullah; Mufidah, Mufidah (JHP17 (Jurnal Hasil Penelitian), 2019)
The enthusiasm as the user of the room in the building can work well and comfortably, if in the building get enough lighting in accordance with the function of the room. Lighting in buildings comes from natural lighting, the source of which is sunlight and artificial lighting from light bulbs. The use of natural lighting in buildings, in addition to not having too much heat in the room, can also reduce the cost of using electricity. There are a lot of lecture rooms at Untag Surabaya campus, if in each lecture room can use natural lighting in the building, it will certainly be able to reduce the operational costs quite a lot. In this study, studio B's lecture room was selected in Untag Surabaya Architecture, to be simulated using Ecotect 5.5 software to obtain optimal natural lighting in the building. The building variables used as modifiers are window proportion, window position, color change, change in ceiling height, as well as the difference in the base of the building. The final results of this study are expected to get optimal classroom recommendations for learning by using natural lighting, so as to reduce the cost of using electricity. Â Keywords : natural lighting, studio class room, saving electricity energy K